Religious Inclusivity: A Study of Non-Artificial Social Interaction in Senduro Village, Lumajang Regency - Azizah Alie; Umar Sholahudin (Cita konsultindo, 2026)
This study examines religious inclusivity through non-artificial social interactions from the perspective of the sociology of religion, focusing on the lived religious experiences of the Senduro Village community in Lumajang Regency, East Java. In Indonesia’s plural religious landscape, social harmony among religious groups often relies on formal regulations and symbolic tolerance. However, Senduro Village presents a distinctive case in which interreligious harmony is sustained through organic, everyday social practices rooted in historical experience, cultural traditions, and collective consciousness. Using a qualitative descriptive approach with a case study method, this research explores how non-artificial social interactions shape inclusive religious life. Data were collected through participant observation, in-depth interviews with religious leaders, community figures, and residents from different religious backgrounds, as well as documentation of social and religious activities. The data were analyzed thematically using qualitative triangulation to capture the social meanings embedded in interreligious relations. The findings reveal that religious inclusivity in Senduro is not merely symbolic but is deeply embedded in social practices such as mutual cooperation (gotong royong), shared participation in religious and cultural rituals, and collective economic activities. Interfaith involvement in traditions like the Ogoh-Ogoh procession, Jolen ritual, and village communal events illustrates how religious differences are negotiated through everyday interactions rather than institutional arrangements. From a sociological perspective, these practices function as social capital, reinforcing trust, solidarity, and moral commitment across religious boundaries. This study concludes that non-artificial social interactions play a crucial role in sustaining long-term religious harmony. Senduro Village serves as a sociological model of inclusive religiosity, demonstrating how local wisdom and historically rooted social relations can strengthen social cohesion and religious moderation in plural societies.